Sustained yield as an objective of Malaysian forest management - Mohd, Rusli; Hadi, Yusuf; Mohamed, Shukri; Muktar, Ashari; Abdul Ghani, Awang Noor (1987)
The paper reviews the concept of sustained yield, assesses its advantages and disadvantages, and attempts to put into perspective its application in managing the forest of Malaysia and Southeast Asia. The concept is traced from its beginning in early European Forestry, through its various developments in North America, to its introduction to forestry thinking in Malaysia. Its alleged advantages and disadvantages are synthesized from the on-going debate on the concept in the forestry literature, and suggestions for the improvement of the concept are discussed. The form of sustained yield which should be used as an objective in Malaysian forest management is suggested. Its main features should be applicable to forest management in the other nations of Southeast Asia and the Tropics.